Residual Activity of Metarhizium anisopliae or Plant Extracts on Laying Hens for Menacanthus stramineus Lice Control by Dipping - Pablo, E.S.; Sandoval, A.L.M.; Fernandez, M.R.; Morales, E.; Prado, O.; Tellez, G.; Quintero, M.T.M. (International Journal of Poultry Science, 2009)
In the present study, eighty-four Hy-Line W36 laying hens in two experiments were distributed in 7 treatments with 3 replicates of four hens each. Each treatment, hens received 3 dipping/2 min every 48 h. Residual activity was done by counting lice one month after dipping. Treated hens with no live lice were reinfested with 20 lice and repeated during three months. In experiment one, aqueous suspensions of three plant extracts were tested as dips for control of MS lice: a) Neem (Azadirachta indica) 500 ppm; b) Ruda (Ruta graveolens) 11,700 ppm; or c) Solanacea (Ardisia solanacea) 50,000 ppm; d) Negative Control (water). After the first dipping, a significant difference (p